PERAN WAKAF PRODUKTIF TERHADAP KESEJAHTERAAN UMAT MELALUI BAITURRAHMAN MART LHOKSEUMAWE - Damanhur; Yuliana (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine the role of Productive Waqf empowered at Baiturrahman Mart on the surrounding community and also on the mosque. This type of research is qualitative descriptive research using primary and secondary data. The data collection techniques used are in-depth interviews, participant observation, and documentation. Descriptive data analysis uses the Miles and Huberman theory. The results of this study show that productive waqf has a role and impact on the surrounding community/congregation, including Baiturrahman Mart being able to reduce unemployment, accommodate MSME products, distribute basic foodstuffs to regular congregants, and even help the economy of the Baituraman Mosque. Based on the available data, Baiturrahman Mart's highest turnover was in May 2024 (Shawwal 1444 AH), where the turnover reached 192,874,400 with a profit of 171,690,965. As an economic driver for the mosque, Baiturrahman Mart has already made significant contributions despite not yet reaching its haul (annual turnover calculation for a minimarket). Once it reaches its haul, it is hoped that it will provide additional contributions to the prosperity of Baiturrahman Mosque and positively impact the welfare of the congregation and surrounding community.